METHODS OF TEACHING WORDS AND CONVERSATIONAL PHRASES IN ENGLISH TO PRESCHOOL-AGED CHILDREN - Axunjanova Muslima (TADQIQOTLAR, 2025)
Abstract: This article examines effective methods for teaching English vocabulary and conversational phrases to preschool-aged children, emphasizing the importance of early language exposure and developmentally appropriate pedagogical strategies. Drawing on contemporary research in early childhood education, second language acquisition, and communicative methodology, the study highlights how multisensory learning, play-based activities, storytelling, action-based techniques, and interactive routines can significantly enhance children’s receptive and productive language skills. The article also investigates the cognitive and socio-emotional characteristics of preschool learners, demonstrating how their natural curiosity, imitation skills, and sensitivity to rhythm and repetition make them highly responsive to immersive and communicative approaches. Through an analysis of practical techniques such as Total Physical Response (TPR), thematic games, realia-based instruction, songs, chants, and classroom rituals the study outlines a framework for creating engaging and meaningful learning environments. Additionally, the article addresses challenges commonly encountered in teaching young learners, including short attention spans, limited metalinguistic awareness, and the necessity of consistent exposure. The findings suggest that playful, interactive, and context-rich instruction not only accelerates vocabulary acquisition but also fosters confidence, motivation, and positive attitudes toward English learning at an early age.